Protein arginine N-methyltransferase 1 promotes the proliferation and metastasis of hepatocellular carcinoma cells - Qing Gou; ShuJiao He; ZeJian Zhou (Tumor Biology, 2017)
Hepatocellular carcinoma is the most common subtype of liver cancer. Protein arginine N-methyltransferase 1 was shown to be upregulated in various cancers. However, the role of protein arginine N-methyltransferase 1 in hepatocellular carcinoma progression remains incompletely understood. We investigated the clinical and functional significance of protein arginine N-methyltransferase 1 in a series of clinical hepatocellular carcinoma samples and a panel of hepatocellular carcinoma cell lines. We performed suppression analysis of protein arginine N-methyltransferase 1 using small interfering RNA to determine the biological roles of protein arginine N-methyltransferase 1 in hepatocellular carcinoma. In addition, the expression of epithelial-mesenchymal transition indicators was verified by western blotting in hepatocellular carcinoma cell lines after small interfering RNA treatment. Protein arginine N-methyltransferase 1 expression was found to be significantly upregulated in hepatocellular carcinoma cell lines and clinical tissues. Moreover, downregulation of protein arginine N-methyltransferase 1 in hepatocellular carcinoma cells by small interfering RNA could inhibit cell proliferation, migration, and invasion in vitro. These results indicate that protein arginine N-methyltransferase 1 may contribute to hepatocellular carcinoma progression and serves as a promising target for the treatment of hepatocellular carcinoma patients.